Tolerability of Capsaicinoids from Capsicum Extract in a Beadlet Form: A Pilot Study - Jayant Deshpande; Shankaranarayanan Jeyakodi; Vijaya Juturu (Journal of Toxicology)
A single center, open-label, dose-finding adaptive study was conducted in twelve healthy overweight female subjects. The study was to evaluate the safety and tolerability of the capsaicinoids (CAPs) from Capsicum extract in a beadlet form compared to placebo in a healthy overweight population. The investigational product capsaicinoids (CAPs) from Capsicum extract in a beadlet form (Capsimax®) a proprietary encapsulated form of Capsicum extract in beadlet form supplemented at 2 mg, 4 mg, 6 mg, 8 mg and 10 mg of CAPs. An ascending dose protocol evaluated a total dose of 10 mg daily given in five divided doses (2 mg, 4 mg, 6 mg, 8 mg and 10 mg of CAPs). Each dose was given for a week. Safety and tolerability were assessed. Primary outcomes were tolerability assessments and reports of adverse events. Tolerability assessments were observed on skin color and any changes in skin, bowel movement, digestion, mouth or throat, hair color or changes in hair color, urination includes frequency and burning sensations, breathing, any changes in their health. Secondary outcomes were body weight, body mass index (BMI), blood pressure (SBP/DBP), vital signs, electrocardiograms, clinical chemistry parameters including liver function tests, lung function tests and kidney function tests and complete blood count (CBC). No dose effective changes were observed. The escalating dose levels of CAPs in a beadlet form product found was tolerable and safe for weight management studies. Tolerability assessments and safety blood markers showed no significant changes from baseline. No significant serious adverse events were reported throughout the duration of the study. Further longer term studies are required to explore the tolerability of the product. This trial is registered with ISRCTN: #  ISRCTN10975080.